2022
DOI: 10.3758/s13414-022-02629-6
|View full text |Cite
|
Sign up to set email alerts
|

Attentional capture is modulated by stimulus saliency in visual search as evidenced by event-related potentials and alpha oscillations

Abstract: This study used a typical four-item search display to investigate top-down control over attentional capture in an additional singleton paradigm. By manipulating target and distractor color and shape, stimulus saliency relative to the remaining items was systematically varied. One group of participants discriminated the side of a dot within a salient orange target (ST group) presented with green circles (fillers) and a green diamond distractor. A second group discriminated the side of the dot within a green dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 122 publications
0
0
0
Order By: Relevance
“…Therefore, more suppression is expected to prevent the potentially stronger attentional capture by more salient distractors. However, Forschack, Gundlach, Hillyard, and Müller (2023) found that the distractorelicited P D was unaffected by distractor saliency. Similarly, the contralateral alpha amplitude was unaffected.…”
Section: By Matthias M Müller and Dirk Kerzelmentioning
confidence: 86%
“…Therefore, more suppression is expected to prevent the potentially stronger attentional capture by more salient distractors. However, Forschack, Gundlach, Hillyard, and Müller (2023) found that the distractorelicited P D was unaffected by distractor saliency. Similarly, the contralateral alpha amplitude was unaffected.…”
Section: By Matthias M Müller and Dirk Kerzelmentioning
confidence: 86%
“…Theta oscillations are linked to recognition memory encoding and retrieval (Klimesch et al, 2001). Evoked alpha waves are associated with inhibitory processes, suppressing non-relevant brain areas for task performance, directing attentional processes, and reflecting sensory processing and encoding (Ehlers et al, 2015;Mathewson et al, 2014;Forschack et al, 2023). Evoked beta oscillations are associated with motor actions and their inhibition, anticipation of a stimulus, and sensory feedback and evaluation of outcomes (Del Campo-Vera et al, 2022).…”
mentioning
confidence: 99%